Study of Interaction of Shallow Groundwater and River along the Cisadane and Ciliwung River of Jakarta Basin and Its Management using Environmental Isotopes - Sidauruk, Paston; Syafalni; Satrio (Jurnal Ilmiah Aplikasi Isotop dan Radiasi, 2013)
The environmental isotopes were employed to study the interaction of shallowgroundwater and river along the Cisadane River and Ciliwung River in Jakarta basin. Therapid growth and development of Jakarta and its surrounding cities, coupled with increasingindustrial and other business sectors have impacted on the demand of the water supply forthe area. These investigations have been conducted to determine the interaction betweenshallow groundwater and the river. The 14C results showed that the groundwater samples(above 40 m) which were close to the river influenced the iso-age contour of 14C, whichindicated the contributions of river water. The analysis of stable isotopes 18O and Deuteriumfrom the river implied that the river water from upstream to downstream was influenced bythe mixing of the river water with the human activities in the upstream (the isotopiccompositions becoming enriched). Further, the 18O and Deuterium data revealed that rivers ofCisadane and Ciliwung are contributing to recharge the shallow groundwater in Jakarta,especially in the nearby river bank. In general, the quality of the shallow groundwater alongthe rivers is good and is suitable as fresh water resource. Due to pollution and declining watertable problems in the Jakarta basin, the artificial recharge wells is shown to be a good wayout to delineate the problems as indicated by pilot project conducted at Kelurahan KramatJati, using infiltration basin method.